HARZBURGITE MELTING WITH AND WITHOUT H2O: EXPERIMENTAL DATA AND PREDICTIVE MODELING - Parman S.W.; Grove T.L. (My University, 2004)
The effect of H2O on harzburgite-saturated melts has been quantified with a series of hydrous and anhydrous melting experiments using a piston-cylinder device. Experimental conditions were 1.2–2.2 GPa and 1175–1500°C. Melt H2O contents range from 0 to 10 wt %. The effects of temperature, pressure, and bulk composition (including H2O) on the SiO2 content of the experimental melts have been evaluated using SiO2 activity coefficients. The results suggest a two-lattice-type model for the melt phase in which H2O mixes nearly ideally with other network modifiers (MgO, FeO, etc.) but does not mix on the network-forming lattice site and so has little effect on SiO2 activity coefficients. The effect of H2O on SiO2 activity is too small to produce the high SiO2 contents observed in mafic andesite magmas. It is proposed that the SiO2-rich character of hydrous, subduction-related magmas is the result of the low temperatures at which hydrous melting occurs relative to anhydrous melting. Partition coefficients for MgO and FeO increase at lower temperatures, while the partition coefficient for SiO2 is nearly constant and is buffered by olivine-orthopyroxene equilibria. Therefore the SiO2/(MgO + FeO) ratios of harzburgite saturated melts increase as temperature falls in both hydrous and anhydrous systems. The results suggest that H2O contents of andesitic magmas may be far higher (>7 wt %) than is generally accepted. Experimentally measured mineral/melt partition coefficients (this study and literature data) have been parameterized in terms of pressure, temperature, and melt H2O content. These expressions have been used to construct a Gibbs-Duhem-based numerical model that predicts the compositions of hydrous and anhydrous olivine-orthopyroxene-saturated melts. Comparisons with experimental data not included in the model indicate that it is the most accurate model available for predicting the compositions of high-degree mantle melts, with or without H2O.
Keywords: mantle; melting; harzburgite; high-pressure; experimental; hydrous